Status of Kirati Languages In The Context of Nepalese Languages - Tumbahang, Govinda Bahadur (Tribhuvan University Journal, 2016)
This article highlights the linguistic scenario of multilingual Nepal, and measures the vitality levels of overall languages in general and Kirati languages in particular on the basis of Expanded Graded Intergenerational Disruption Scale (EGIDS) used by Lewis and Simons(2010) derived from Fishman's Graded Intergenerational Disruption Scale (GIDS 1991). The first part presents the linguistic situation of Nepal, the second part demonstrates the vitality levels of Nepalese languages in general, the third part indicates the status of Kirati languages and the last part provides some suggestions.